1974
DOI: 10.1172/jci107763
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Catecholamines and Carbohydrate Metabolism in Patients with Acute Myocardial Infarction

Abstract: A B S T R A C T Blood glucose, glucose tolerance, serum insulin, free fatty acids in serum, plasma noradrenaline, and plasma adrenaline were measured in 10 patients with acute myocardial infarction (AMI) as well as in healthy subjects. Both noradrenaline and adrenaline in plasma were elevated in patients with AMI, the level being fairly constant in the individual patients and dependent on their degree of illness.In the fasting state, blood glucose, serum insulin, and free fatty acids were elevated in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…The plasma epinephrine concentrations resulting from these infusion rates have been measured previously in a group of 40 patients under circumstances similar to those in the present study and were found to fall within the range of plasma epinephrine concentrations that occurs during a wide variety of stresses in humans.1 Ten minutes of infusion are required to attain a steady-state plasma epinephrine concentration,5,6 and, therefore, to ensure that steady-state conditions had been achieved, epinephrine was infused for 14 minutes before its electrophysiologic effects were measured. There were no adverse reactions to the infusion of epinephrine.…”
Section: Infusion Of Epinephrinesupporting
confidence: 73%
“…The plasma epinephrine concentrations resulting from these infusion rates have been measured previously in a group of 40 patients under circumstances similar to those in the present study and were found to fall within the range of plasma epinephrine concentrations that occurs during a wide variety of stresses in humans.1 Ten minutes of infusion are required to attain a steady-state plasma epinephrine concentration,5,6 and, therefore, to ensure that steady-state conditions had been achieved, epinephrine was infused for 14 minutes before its electrophysiologic effects were measured. There were no adverse reactions to the infusion of epinephrine.…”
Section: Infusion Of Epinephrinesupporting
confidence: 73%
“…The possibility that WISP-1 may act early during the acute phase of myocardial injury is suggested not only by its responsiveness to TNF-␣ and IL-1␤ but also by the observation that cAMP induction by ␤-adrenergic agonists or forskolin treatment was shown to block CTGF expression (14). Catecholamines increase rapidly in the heart post-MI, leading to elevated cAMP levels that then decrease gradually over time (15,39,41). We observed rapid upregulation of WISP-1 in the heart post-MI where transcripts appeared as early as 6 h and protein levels were significantly elevated by 24 h. This induction occurred at a time when elevated cAMP levels would likely preclude CTGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown (66) that these rates (the latter approximately equal to the former for a 70-kg subject) produce circulating norepinephrine levels in the range of 1,400-2,100 pg/ml, at which level we also saw an increase in plasma glycerol. Although this norepinephrine range is reached during exercise (61), and with illnesses such as ketoacidosis (63) and myocardial infarction (67), it is rarely approached under ordinary physiological circumstances. Thus, under usual conditions, it appears that the lipolytic actions of norepinephrine may be limited to its long recognized local effector role as sympathetic neurotransmitter at nerve endings in adipose tissue.…”
Section: Methodsmentioning
confidence: 99%